Plan estratégico para la ampliación y remodelación del centro de belleza d’carmen “stilos” de la ciudad de Quevedo, año 2015 - Holguín Pérez, Carmen Annabel (2015)
The strategic plan represents for companies an important tool to achieve its objectives and goals. This research is part of the implementation of a strategic plan for the expansion and renovation of Centro de Belleza D'CARMEN "STILOS", dedicated to providing aesthetic services to the population of Quevedo. With about three years of operation D'CARMEN "STILOS" he has gained market share aesthetic services. It currently has a large number of customers, which has raised concerns in the manager - owner, because today it is difficult to develop the different services in a space that is currently small. The first step in the research was to develop a market study in order to determine the unmet demand for beauty services and to establish the niche market to which should arrive D'CARMEN "STILOS". Later this matrix was designed SWOT listing the internal and external factors that affect the performance and normal functioning of Beauty Center, where they were identified as key strengths: professional and highly trained staff, guaranteed service, quality products and affordable prices; while weaknesses presented highlight the lack of equipment with advanced technology, small footprint and limited local advertising media. It is important to note that for much of the information was used to the types of descriptive research, field and literature, considered as primary and secondary research sources; while main methods are deductive, inductive and analytical, which contributed to the problem definition, analysis of the assumptions and preparing the strategic plan. By developing a strategic plan D'CARMEN "STILOS" may enhance their products and beauty services in a better way its customers, through the project for expansion and remodeling Beauty Center will have more physical space to provide its different services. Which will help to improve their corporate image and also incorporate new aesthetic services